2009
DOI: 10.1007/s00011-009-8230-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platelet release products on neutrophilic activity in human whole blood

Abstract: These data suggest that the neutrophilic activity enhanced by PRPr depends more on ATP and ADP during the early phase and on MAPPs during the later phase of the phagocytic process. The present study reveals an important role for PRPr and their phagocytosis activators in the enhancement of neutrophilic activity in human whole blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…In a flow cytometric analysis of phagocytosis using whole blood, plateletrelease products and MAPPs showed the activation of phagocytosis (Wu et al 2009), similar to that observed in experiments using Terasaki microplates.…”
Section: Effects Of Platelet-release Products and Mapps On Neutrophilsupporting
confidence: 75%
See 2 more Smart Citations
“…In a flow cytometric analysis of phagocytosis using whole blood, plateletrelease products and MAPPs showed the activation of phagocytosis (Wu et al 2009), similar to that observed in experiments using Terasaki microplates.…”
Section: Effects Of Platelet-release Products and Mapps On Neutrophilsupporting
confidence: 75%
“…In some experiments, a flow cytometric study using whole blood was performed to assess phagocytosis (Wu et al 2009). Briefly, 100 μL of heparinized venous blood was mixed with 100 μL of a stimulant prepared in RPMI 1640 supplemented with 1% bovine serum albumin, and the phagocytosis of FITClabeled E. coli (Sigma, St Luis, MO, USA) was assessed by measuring neutrophilassociated fluorescence with a flow cytometer (EPICS ® XL, Coulter Corp., Hialeah, FL, USA).…”
Section: Phagocytosis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, microparticles have been reported to be released in stored platelets [72,73] and have recently been impressively demonstrated in apheresis platelets [74]. In addition, in stored platelets, indirect evidence suggests the release of ATP [75,76,77]. Microparticles have also been detected in fresh frozen/thawed plasma [78,79,80] (table 1).…”
Section: Trali Pathogenesis In Light Of the Innate Immune Systemmentioning
confidence: 99%
“…Antiphospholipid antibodies, particularly anticardiolipin antibodies, have been associated with various neuropsychiatric manifestations [3,4,5,6]. Currently, the descriptions of epileptic seizures in patients with SLE are poorly defined.…”
Section: Introductionmentioning
confidence: 99%